Resilience Gentrification: Environmental Privilege in an Age of Coastal Climate Disasters - Gould, Kenneth A.; Lewis, Tammy L. (Frontiers in Sustainable Cities, 2021)
Climate change is exacerbating storms at the same time that humans are increasingly settling in areas most affected by such storms. In theory, post-disaster recovery offers opportunities to rebuild for sustainable development. However, in reality, responses to climate events often result in greater inequality through a process we term resilience gentrification. Three possible resolutions to the coastal resilience dialectic are managed retreat, denial, and structural mitigation. Structural mitigation has become the most popular response in the Anthropocene. This response raises the cost of coastal redevelopment, giving capital greater access and control over development decisions. These changes make coastal areas more expensive and more exclusive. We illustrate this process in the post-disaster recovery of two very different communities: Gowanus, Brooklyn and the Caribbean island of Barbuda. In both cases, attempts to build it back “green”—using selective aspects of “sustainable development” as a guide—come at the cost of exacerbating existing housing inequality. In this way, “resilience” gets equated with wealth, thus reinforcing a cycle of climate injustice. To achieve a “just sustainability,” government responses must consider and address the equity impacts of climate change resilience policies. Managed retreat and degrowth strategies for climate resilience offer greater potential for a just sustainability in the Anthropocene.